A therapeutic approach to pantothenate kinase associated neurodegeneration. Issue 1 (December 2018) - Sharma, Lalit; Subramanian, Chitra; Yun, Mi-Kyung; Frank, Matthew; White, Stephen; Rock, Charles; Lee, Richard; Jackowski, Suzanne
Abstract Pantothenate kinase (PANK) is a metabolic enzyme that regulates cellular coenzyme A (CoA) levels. There are three humanPANK genes, and inactivating mutations inPANK2 lead to pantothenate kinase associated neurodegeneration (PKAN). Here we performed a library screen followed by chemical optimization to produce PZ-2891, an allosteric PANK activator that crosses the blood brain barrier. PZ-2891 occupies the pantothenate pocket and engages the dimer interface to form a PANKATPMg2+ PZ-2891 complex. The binding of PZ-2891 to one protomer locks the opposite protomer in a catalytically active conformation that is refractory to acetyl-CoA inhibition. Oral administration of PZ-2891 increases CoA levels in mouse liver and brain. A knockout mouse model of brain CoA deficiency exhibited weight loss, severe locomotor impairment and early death. Knockout mice on PZ-2891 therapy gain weight, and have improved locomotor activity and life span establishing pantazines as novel therapeutics for the treatment of PKAN. Mutations in pantotenate kinase (PANK) cause neurodegneration. Here the authors carry out achemical screen and identify a PANK activator that is orally available, crosses the blood brain barrierand show that it effecttive in improving pathology and life span in a mouse model of the disease.